Pendidikan Lingkungan dan Taman Nasional: Strategi Konservasi Dunia dan Kegiatan Interpretasi Alam - Daniel H Henning; Ani Pakpahan (Media Konservasi, 1991)
This paper deals with environnlental education aspects of National Parks in ternts of the World Consen~ationS tmtegy (W CS), values, and nahlralist interpretive activities.National Parks can provide the "nanrre" or natural environnlent base for environmental education. Vahies need to be enlphasized when dealing with environmental education in National Park The three inlpol-rant objectives/vahres of the WCS sho~lldb e applied to National Park and associated environntental edrlcationefforts. In addition, some ecological principles can be applied to environmental education activities. "Thinking ecologically" is a vital part of environntental education. As part of environntental education, naturalist interpretive actitities arepresented with challenges to interpret how living resources (particcilar!~ through the WCS), can contribute to public rinderstanding and support for consemation maesuresoutside National Park. Sonre suggestions for nzeeting the challenges are discussed. The paper is also presented sonle of National Parh values.